Domestic violence features in pregnant women Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2022)
With the aim of determining the features of domestic violence during pregnancy in women admitted to the Obstetrics Service of the Hospital Central Universitario Dr. Antonio María Pineda during the month of February 2019, a transversal descriptive study was carried out with a sample of 150 patients obtaining a frequency of domestic violence of 17.3%. 73% of patients had ages between 16-25 years old, from urban background (92.3%), single (76.9%), with high school level of education (69.2%), housewife (100%) with no income (100%). The type of domestic violence was mainly psychological (80.7%), followed by physical (69.2%) and sexual (34.6%). The main aggressor was the husband or partner (92.3%) being the moment of the aggression frequently at the beginning of the pregnancy (88.4%). The practices assumed in the face of domestic violence showed that 100% of the women interviewed did not seek family or health personnel support and did not report the incident. In addition, 100% said they did not need medical or psychological attention. As a result, there is a high percentage of women victims of domestic violence that don’t report or seek medical o psychological attention. Therefore, it’s important to create domestic violence awareness in the pregnant women and expose the reality of this problem to face this alarming situation.
Keywords: domestic violence; violence against women; intimate partner violence; pregnancy; sex offenses